Ensuring Security in Economic Freedom: A Cross Case Between Indonesia's Border Neighbors - Diana Lestari; Syarifah Hudayah; Irwansyah Irwansyah (Jurnal Ekonomi dan Studi Pembangunan, 2023)
An open economy allows for partnerships between countries. The urgency of this paper is to dedicate the government's concern to revitalizing weapons in finance, export–import, and empowering the military sector to maintain economic freedom in 8 countries. The objectivity of the study focuses on Indonesia's cross–border countries. Annual published data sourced from the Global Economy is compiled for 6 periods. Then, the comparative linear regression technique serves to articulate the analysis funds. Since 2016–2021, there are indications that there is a strong determination of arms imports, arms exports, GDP of the military, armed forces personnel, and military spending on economic freedom. Interestingly, it was found that variables that influence economic freedom include arms imports in Australia, Papua New Guinea and the Philippines, then arms exports in Indonesia, Australia and Papua New Guinea. In line with the GDP of the military which also affects economic freedom for Indonesia, Papua New Guinea, Singapore and Thailand. Furthermore, only armed forces personnel have a systematic effect on Australia and Vietnam and military spending on Papua New Guinea and Malaysia. Therefore, the research output guides future studies to consider protective national military policy interventions as an alternative to driving national economic independence.